Análise do nível de conhecimento tático declarativo e de aptidão física em atletas juvenis de handebol - Viveiros, Vanessa Vieira (2023)
Introduction: For an athlete to be successful in sports, he must have adequate preparation. Handball is characterized by rapid transitions between offensive and defensive actions during the game with the goal of scoring goals. Studies indicate that both the level of declarative tactical knowledge (DTC) and the level of physical fitness (FPA) of the athlete can influence sport performance. Objective: To analyze the level of CTD and APF in juvenile handball athletes and the correlation between these variables. Methodology: The sample was composed by 16 male athletes, members of a state handball team, selected by convenience, with mean age of 16.69 (±0.60) years. The Test of Declarative Tactical Knowledge (TCTDHb) was applied to verify the athletes' levels of perception and decision making. The Projeto Esporte Brasil (PROESP-Br) protocol was also applied to assess the level of physical fitness. The analyzed variables were divided into somatic: stature (1.77m ± 0.07), wingspan (1.87m ± 0.07), body mass (75.70kg ± 19.40) and waist circumference (0.82m ± 0.13); motor performance variables: agility, flexibility, abdominal endurance strength, upper limbs explosive strength, lower limbs explosive strength, cardiorespiratory endurance, and speed. Descriptive statistics were used to help characterize the sample. All variables were tested for normal distribution of data using the Shapiro-Wilk test, with a significance level of p<0.05. The absolute and relative frequencies were used to indicate the percentage of the classification zone according to the criteria used. Spearman's Correlation test was performed between CTD and APF. Results: The body mass index of the analyzed group had a mean of 24.05 ± 5.71 kg/m2 pointing eutrophy (68.8%) and the waist to height ratio the mean was 0.82 ± 0.13 cm, healthy zone (81.2%). Regarding the CTD level of the analyzed athletes, it was observed an average of 2.50 ± 1.03 correct answers. The potentials reached by the athletes fall into the weak potential (50%) and evolving potential (50%), which identifies that the athletes are still in the handball learning phase. According to the result of the applied correlation test it was possible to see that the components of APF and CTD did not present significant correlations (CTD x agility: ⍴ = - 0.17 and p = 0.53; CTD x flexibility: ⍴ = - 0.43 and p = 0. 09; CTD x lower limb strength: ⍴ = - 0.40 and p = 0.12; CTD x lower limb strength: ⍴ = - 0.07 and p = 0.79; CTD x cardiorespiratory endurance: ⍴ = - 0.16 and p = 0.54; CTD x muscular endurance: ⍴ = - 0.05 and p = 0.86; CTD x speed: ⍴ = 0.42 and p = 0.10. Final considerations: The results obtained showed the level of APF and CTD of the investigated subjects being possible to identify variables that need to be improved, as well as the absence of correlation between these variables, thus highlighting the importance of the expansion of knowledge about APF and CTD within a context of sports performance.